Windows 10 Primer What to Expect from Microsoft's New Operating System - Halsey, Mike (Apress : Imprint: Apress, 2015)
With Windows 10 arriving later in 2015, many questions remain to be answered, both for businesses and home users. Will it provide the compatibility of Windows XP, and the usability of Windows 7? Will it banish forever the problems associated with Windows 8? In this book, Windows expert, author and MVP Mike Halsey answers the questions you have and details hidden and improved features that can revolutionize your security, productivity and user experience. Whether you're an IT professional considering or planning an upgrade to your company's PCs or a Windows enthusiast eager to find out if Microsoft has finally built a truly modern Windows experience, Windows 10 Primer has the answers to all your most important questions.